The Effect of Church Community Development and Pastoral Services on The Growth of The Congregation of The Bethel Indonesia Church, Family Blessing Surabaya - Kasiatin Widianto; Surja Permana; Juanda Juanda (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2019)
The existence of the church in this world is God's plan and will. Like a plant, which naturally grows and develops; as is the case with the existence of the church, God desires that His church grow and develop both in quality and quantity. There are various factors that influence the growth of the church, including the presence of church members and good pastoral care for the people. This research to describe the influence of church building and pastoral care on the growth of the congregation of the Bethel Indonesia Church “Family Blessing” Surabaya. Apart from that, to find out how much influence each independent variable has on the dependent variable. The approach used in this research is quantitative; where the population which is the object of this research is 400 members of the Bethel Indonesia Church “Family Blessing” Surabaya. The sample is taken from a population of 24% or 96 people who can represent the population with a simple random sampling technique. The data collection technique uses an instrument in the form of a questionnaire to collect data on three variables, namely: (1) fostering church members, (2) pastoral care, and (3) church growth. The results of the study showed: (1) the influence of coaching church members on the growth of the congregation of the Bethel Indonesia Church “Family Blessing” Surabaya was in the medium category. (2) the influence of pastoral care on the growth of the congregation of the Bethel Indonesia Church “Family Blessing” Surabaya in the medium category. And (3) the influence of coaching church members and pastoral care together on the growth of the congregation of the Bethel Indonesia Church “Family Blessing” Surabaya is also in the medium category. Based on the findings in this research, several suggestions were suggested as follows: (1) The formation of church members, with three dimensions, namely Coinonia, Diakonia and Marturia had influence in the medium category. It is recommended that it be maintained, even if the implementation is increased. Because through these three dimensions the resources of the people are included in the ministry. (2) As with the formation of church members, pastoral care also influences the moderate category of church growth, therefore it is recommended that the implementation be increased so that through direct contact with the life of the congregation it will strengthen the spirituality of the church.